Variations in athletic performance with occlusal splint in track and field athletes: a randomized clinical trial - Parrini, S.; Rossini, G.; Nebiolo, B.; Airale, M.; Franceschi, A.; Cugliari, G.; Deregibus, A.; Castroflorio, T. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Several studies have been proposed with the aim to demonstrate correlations between the dento-mandibular apparatus and the skeletal muscle system of the human body even in regions distant from the oral cavity. However, a definite conclusion cannot be drawn. The aim of this paper is to demonstrate a possible correlation between dental occlusion and sport performances in track and field athletes. METHODS: Sixteen track and field athletes were enrolled for the study and were randomly divided in three groups: Untreated control group, Placebo group (with a lower plaque without occlusal coverage) and Treated group (with occlusal splint). Changes in sprint and jump performance were assessed on a weekly basis for 5 consecutive weeks, during which athletes had to wear oral devices, except for the first week of baseline, for at least 3 trainings lasting 2 hours per week . All participants performed the countermovement jump (CMJ), the drop jump (DJ), the 10m and 30m sprint tests, always on the same day on the week. RESULTS: No statistically significant difference resulted between Control group and Placebo group and between Control group and Treated group. However, it was possible to observe a clinical improvement of measurements obtained, especially for CMJ, 10m and 30m sprint tests. No variation neither statistical neither clinical was observed in DJ test analysis. CONCLUSIONS: Even if statistically it was not possible to demonstrate an improvement in sport performance, most of the athlete analyzed showed better results during training session with occlusal splint compared to athlete without occlusal splint, in countermovement jump, in 10m and 30m sprint tests.